Immunohistochemical analysis of adenocarcinoma of the small intestine: a tissue microarray study. Issue 12 (25th November 2003) - Svrcek, M; Jourdan, F; Sebbagh, N; Couvelard, A; Chatelain, D; Mourra, N; Olschwang, S; Wendum, D; Fléjou, J-F
Abstract : Background: Primary adenocarcinomas of the small intestine are rare, and the genetic mechanisms involved in their carcinogenesis remain unclear. Aim: To examine the expression of candidate proteins in small intestinal adenocarcinomas by immunohistochemistry performed on tissue microarrays (TMAs). Methods: Twenty seven primary sporadic small intestinal adenocarcinomas were analysed. The TMA technique was validated by comparing immunohistochemical labelling of hMLH1 and hMSH2 on TMAs and the tissue sections they derived from. The expression of Smad4, hMSH6, β catenin, and p53 was investigated and results compared with those obtained in 14 malignant ampullary tumours. Results: TMA technology with threefold redundancy adequately represented the immunohistochemical pattern of small intestinal adenocarcinomas. Loss of hMLH1 expression, but not hMSH2 or hMSH6, was seen in two of 27 small intestinal adenocarcinomas. All ampullary tumours showed nuclear staining for hMSH2 and hMSH6. One case showed lack of immunostaining for hMLH1. Smad4 expression was absent in five small intestinal adenocarcinomas and two ampullary tumours. Overexpression of p53 was detected in the nuclei of 14 of the 27 small intestinal adenocarcinomas, and five of the 14 ampullary tumours. Nuclear or cytoplasmic expression of β catenin was present in all specimens. Conclusion: Inactivation of the SMAD4/DPC4 gene seems to be involved in small intestinal adenocarcinoma tumorigenesis. Overexpression of p53 and abnormal expression of β catenin are two common events, unlike the loss of expression of the DNA mismatch repair proteins (hMLH1, hMSH2, and hMSH6). The carcinogenetic process appears to be similar in small intestinal adenocarcinomas and malignant ampullary tumours.